Association of major depression with blood pressure and vascular complications of type 2 diabetes mellitus - Rajender, Akash; C., Deepa; Kanwal, Krishna; Chaudhri, R. S.; Rajender, Gaurav; Choudhary, Priyanka (International Journal of Research in Medical Sciences, 2016)
Background: The WHO estimates the diabetic population to increase to 366 million by 2030 worldwide, with maximum 79.4 million Indians. Depression is an undiagnosed co-morbidity leading to significant disability, non-compliance and postulated to cause poorer glycemic control leading to early disease complications. We aimed to detect depression and study its correlation with vascular complications among type 2 diabetes mellitus (T2DM) patients. Methods: In an observational study, 312 randomly selected T2DM patients were evaluated at tertiary care center in Northern India. Socio-demographic, clinical and laboratory data was collected. Montgomery Asberg depression rating scale (MADRS) was used to detect depression. Groups with and without major depression were compared for various diabetes variables. Statistical analysis was carried out using the SPSS version 14.0. Results: One third T2DM patients (32.05%) suffered from major depression. Depression was significantly associated with diabetic patients having cardiac (p 0.01), ophthalmic (p 0.04), nephropathy (p 0.01), cerebrovascular (p 0.001) complications and diabetic foot (p 0.04). However, depression showed no significant association with systolic blood pressure, neuropathic and infectious complications. Conclusions: Identification of depression and its appropriate management may go a long way in delaying diabetic vascular complications by improving treatment adherence and subsequently glycemic control.